Third Language Acquisition With or Without the Help of English as a Language Support - Ana Mihaela Istrate (European Scientific Journal, ESJ, 2019)
The present study, in the field of third language acquisition, is the result of a three-year research on groups of adult students involved in learning Romanian as a foreign language for the purpose of continuing their academic studies in Romania. This paper focuses on understanding the best methods and techniques for teaching third language. This could apply to groups of international students, whose level of understanding of the English language is A1-A2. The conclusion drawn in this particular case shows that English as a language support has become a useless tool and there is therefore the need to approach the group with a full immersion method. On the other hand, we will discuss aspects related to the cultural background of the target group which dramatically affects the acquisitions of a language whose grammatical structure is extremely different from the first language. At the same time, we will focus on aspects related to the efficiency of teaching with the help of the modern communicative techniques or based on the traditional methods of teaching foreign languages. Based on an analysis of the differences between individuals coming from extremely different cultural backgrounds, we will draw comparisons between the subjects with different language performance. This is an indicator that it is directly related to their long-term objectives. The ultimate role is to raise public attention in the development and adaptation of curriculum content to student achievements, and to find a more successful approach to teaching the L3 to students with lower levels in the L2.